Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class

Ex 9.5

Ex 9.5, 1
Important

Ex 9.5, 2

Ex 9.5, 3 Important

Ex 9.5, 4

Ex 9.5, 5 Important

Ex 9.5, 6

Ex 9.5, 7 Important

Ex 9.5, 8 Important

Ex 9.5, 9

Ex 9.5, 10

Ex 9.5, 11

Ex 9.5, 12 Important

Ex 9.5, 13

Ex 9.5, 14 Important

Ex 9.5, 15

Ex 9.5, 16 Important

Ex 9.5, 17 Important You are here

Ex 9.5, 18 (MCQ)

Ex 9.5, 19 (MCQ) Important

Last updated at May 29, 2023 by Teachoo

Ex 9.5, 17 Find the equation of a curve passing through the point(0 , 2) given that the sum of the coordinate of any point of curve exceeds the magnitude of the slope of the tangent to the curve at that point by 5 We know that Slope of tangent to curve at (x, y) = 𝑑𝑦/𝑑𝑥 Given that sum of the coordinate of any point of curve exceeds the magnitude of the slope of the tangent to the curve at that point by 5 Therefore, |𝑑𝑦/𝑑𝑥| + 5 = x + y |𝑑𝑦/𝑑𝑥| = x + y – 5 𝑑𝑦/𝑑𝑥 = ± (x + y − 5) So, we will take both positive sign and negative sign and then solve it Taking (+) ve sign 𝑑𝑦/𝑑𝑥 = x + y − 5 𝑑𝑦/𝑑𝑥 − y = x − 5 Equation is of the form 𝑑𝑦/𝑑𝑥+𝑃𝑦=𝑄 where P = −1 & Q = x − 5 IF = e^∫1▒𝑃𝑑𝑥 IF = e^(∫1▒〖(−1)〗 𝑑𝑥) IF = 𝑒^(−𝑥) Taking (−) ve sign 𝑑𝑦/𝑑𝑥 = −x − y + 5 𝑑𝑦/𝑑𝑥 + y = −x + 5 Equation is of the form 𝑑𝑦/𝑑𝑥+𝑃𝑦=𝑄 where P = 1 & Q = −x + 5 IF = e^∫1▒𝑃𝑑𝑥 IF = e^∫1▒1𝑑𝑥 IF = e^𝑥 Solution is y(IF) = ∫1▒〖(𝑄×𝐼𝐹)𝑑𝑥+𝑐〗 ye−x = ∫1▒〖(𝑥−5) 𝑒^(−𝑥) 𝑑𝑥+𝑐〗 ye−x = (x − 5) ∫1▒〖𝑒^(−𝑥) 𝑑𝑥〗 −∫1▒〖[1∫1▒〖𝑒^(−𝑥) 𝑑𝑥〗]𝑑𝑥+𝑐〗 ye−x = −(x − 5)𝑒^(−𝑥)−∫1▒〖〖−𝑒〗^(−𝑥) 𝑑𝑥〗 + c ye−x = −(x − 5)𝑒^(−𝑥) + ∫1▒〖𝑒^(−𝑥) 𝑑𝑥〗 + c Solution is y(IF) = ∫1▒〖(𝑄×𝐼𝐹)𝑑𝑥+𝑐〗 yex = ∫1▒〖(5−𝑥) 𝑒^𝑥 𝑑𝑥+𝑐〗 yex = (5 – x) ∫1▒〖𝑒^𝑥 𝑑𝑥〗 − ∫1▒[𝑑/𝑑𝑥(5−𝑥)∫1▒〖𝑒^𝑥 𝑑𝑥〗]𝑑𝑥 yex = (5 − x) 𝑒^𝑥− ∫1▒〖(−1)〗 𝑒^𝑥 𝑑𝑥 yex = (5 − x) 𝑒^𝑥 + ∫1▒〖𝑒^𝑥 𝑑𝑥〗 Integrating by parts with ∫1▒█(𝑓(𝑥) 𝑔(𝑥) 𝑑𝑥) =𝑓(𝑥) ∫1▒〖𝑔(𝑥) 𝑑𝑥 〗−∫1▒〖[𝑓^′ (𝑥) ∫1▒〖𝑔(𝑥) 𝑑𝑥] 𝑑𝑥〗〗 Take f (x) = x – 5 & g (x) = 𝑒^(−𝑥) Integrating by parts with ∫1▒█(𝑓(𝑥) 𝑔(𝑥) 𝑑𝑥) =𝑓(𝑥) ∫1▒〖𝑔(𝑥) 𝑑𝑥 〗−∫1▒〖[𝑓^′ (𝑥) ∫1▒〖𝑔(𝑥) 𝑑𝑥] 𝑑𝑥〗〗 Take f (x) = 5 – x & g (x) = 𝑒^𝑥 ye–x =(5−𝑥)𝑒^(−𝑥) − 𝑒^(−𝑥)+𝑐 Dividing both sides by e−x y = (5 −x) −1 + cex y = 4 − x + cex Since the curve passes through the point (0, 2) Put x = 0 & y = 2 2 = 4 − 0 + ce° 2 = 4 + C C = −2 ∴ Equation of curve is y = 4 − x − 2ex yex = (5 − x) 𝑒^𝑥+ 𝑒^𝑥+𝑐 Dividing both sides by ex y = (5 − x) + 1 + ce−x y = 6 − x + ce−x Since curve passes through the point (0, 2) Put x = 0 & y = 2 2 = 6 − 0 + ce° 2 = 6 + C C = −4 ∴ Equation of curve is y = 6 − x − 4e−x